Stimulating learner engagement in app-based L2 vocabulary self-study: Goals and feedback for effective L2 pedagogy. (April 2022) - He, Xuehong (Stella); Loewen, Shawn
Abstract: Despite its increasing popularity, application-based (app-based) second language (L2) learning faces the persistent issue of low learner engagement. This study explored app-based L2 vocabulary self-study as a course assignment by drawing on Mercer and Dörnyei's (2020) latest proposal of goal-setting with feedback for stimulating learner engagement and motivation. We adopted a quasi-experimental design that consisted of a treatment group who completed goal-setting-and-checking activities ( n = 32) and a control group who did not ( n = 31), and compared learner engagement as indexed by the number of words studied weekly and L2 skill development as assessed by TOEIC scores before and after app use. Ratings and comments were also collected from the treatment group on goal-setting-and-checking activities and from both groups on two supplementary feedback tools, Unfinished Lists (lists of students who did not finish app-based self-study assignments) and leaderboards (student rankings based on assignment performance). Quantitative results showed the treatment group studied more words than the control group, although TOEIC scores did not differ between or change within groups significantly. Quantitative ratings and qualitative comments supported overall positive effects of these three pedagogical interventions. Practical suggestions are provided to guide L2 instructors to adapt these pedagogical interventions into their teaching.